2005
DOI: 10.1063/1.1884758
|View full text |Cite
|
Sign up to set email alerts
|

Conduction mechanisms and reliability of thermal Ta2O5–Si structures and the effect of the gate electrode

Abstract: The effect of metal gate electrodes (Al, W, Au, TiN, and TiN∕W) on dielectric properties, leakage currents, conduction mechanisms, and reliability characteristics of metal-oxide-semiconductor capacitors with thermal Ta2O5 is investigated. The results are discussed in terms of the relative influence of the gate deposition techniques and the intrinsic properties of the electrode material and the former appears to be more pronounced. It is found that some parameters such as interface state density, breakdown fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
1
16
2
Order By: Relevance
“…11. I-V curves for capacitors with various gates [3,16]. dependent on the electrode material regardless that PF mechanism appears to be dominant in the most of the cases.…”
Section: Metal Gates (Integration Challenges)mentioning
confidence: 98%
See 1 more Smart Citation
“…11. I-V curves for capacitors with various gates [3,16]. dependent on the electrode material regardless that PF mechanism appears to be dominant in the most of the cases.…”
Section: Metal Gates (Integration Challenges)mentioning
confidence: 98%
“…One of the key issues here is the control of the electrode work function throughout processing. For example, the effect of various electrodes (Al, W, Au, TiN, TiN/W) on the characteristic of capacitors with Ta 2 O 5 [3,16] shows that some parameters such as interface state densities, breakdown fields and charge trapping are defined by the properties of Ta 2 O 5 itself. The dielectric constant, oxide charge, leakage current at high fields, charge to breakdown and stress-induced leakage currents are remarkably affected by the electrode.…”
Section: Metal Gates (Integration Challenges)mentioning
confidence: 99%
“…The precise description of the behavior of high-k dielectrics requires considering them as stacked high-k/interfacial layer structures. The thickness and the composition of thin interfacial lower-k layer depend strongly on the technological history of the system Ta 2 O 5 /Si (including all annealing steps), and consequently are a subject of a great debate and ongoing investigations [2,5,9,13,15,[17][18][19][20][21][22]. Our structural studies of both RF sputtered and thermally grown Ta 2 O 5 have shown that the interfacial layer is composed of ultrathin SiO 2 and a near interfacial region containing Taand Si-suboxides [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods compatible with silicon technology are successfully developed for obtaining thin films Ta 2 O 5 [2][3][4][5][6][7][8][9]. During the formation of Ta 2 O 5 on Si, however, an interfacial SiO 2 -containing layer is inevitably formed at the Si substrate [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric (1Àx)Pb(Mg 1=3 Nb 2=3 )O 3 -xPbTiO 3 single crystals with composition near the morphotropic phase boundary (x $ 0.33) display large remnant ferroelectric polarization, low coercive field, excellent piezoelectric activity 16 and have perovskite structure with lattice constants a $ b $ c $ 4.02 Å . 17 Because of the good ferroelectric, piezoelectric, and structural properties of (1-x)Pb(Mg 1=3 films can be reversibly modulated via the converse piezoelectric effect of the piezoelectric substrates.…”
Section: Introductionmentioning
confidence: 99%